The Drawing Model Collection of the National Academy of Fine Arts - Sánchez Zumbado, Jimena (2014)
This paper describes the origin and usage of the graphic portion of the oldest collection that the University of Costa Rica owns: the Drawing Model Collection. Which was brought to the country as part of the teaching materials acquired by the Government of Costa Rica for the foundation in 1897 of the National Academy of Fine Arts. This collection of French origin and designed by the master draftsman and painter Bernard Romain Julien (1802- 1871) was a mean used for teaching drawing from which the teachers and students of the first Art Academy in the country fed.